(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A field experiment was conducted in the Faculty of Agriculture,University of Khartoum,( Lat. 15°40ʹ N. Long. 320 32ʹ E). and 380 metresabove sea level. The investigation was for three years, during January toAugust of 2007, 2008 and 2009. The objectives of the experiment were tostudy the effects of the irrigation intervals of 8 days (W1 ) and of 12 days (W 2)on the yield of lucerne fodder, using drip and sprinkler irrigation systems,each of which received 8mm day.-1 The amount per irrigation of W 1 wastherefore 8x8=64mm and that of W 2 was 8x12=96mm .The experimentaldesign was radomized complete block because the geographical site couldnot allow other designs. The results showed that the production of lucerneirrigated at W 1 was higher than that obtained at W 2 by about 70 % from thetotal yield of 2007, 2008 and 2009 by (42 % in drip irrigation and 38 % insprinkler irrigation). During the relatively cool weather (January to March),the yield was more than during the hot weather (April to June). Fodderproduction during the rainy season (July and August) was higher than duringthe hot season. This was probably a result of cloudy and rainy condition.Water use efficiency (WUE) under the W 1 irrigation interval was more thanat the irrigation interval W 2 in each of 2007, 2008 and 2009. The highproductivity was associated with high leaf /stem ratio.